Excessive use of mobile devices and children's physical health. Issue 2 (26th April 2019) - Domoff, Sarah E.; Borgen, Aubrey L.; Foley, Ryan P.; Maffett, Anissa
Abstract: Children's mobile device (e.g., smartphone, tablet) access and ownership has grown substantially in the past decade. Concerns exist regarding excessive use and the impact of frequent consumption of mobile media on children's health and well‐being. We review the literature on the harmful physical health correlates of excessive mobile device use during childhood and adolescence. Strongest evidence emerged regarding the impact of excessive mobile device use and sleep outcomes. Mixed evidence emerged regarding excessive use of mobile devices and physical activity and obesity. Too few studies were identified to draw conclusions about mobile device use and the following health concerns in children: musculoskeletal outcomes/pain, ocular health, and migraine/headaches. Recommendations for future research on the association between excessive mobile device use and children's physical health outcomes (particularly investigations into the experience of musculoskeletal pain/discomfort, ocular symptoms, and neurological symptoms) are discussed.